Advances in wireless and mobile communications (AWMC) (Delhi Research India Publications)
Aims and ScopeThe Advances in Wireless and Mobile Communications (AWMC) provides a forum for research and development (R&D). It is open to all researchers from all kind of universities and organisations in the global, aimed at the increasing important area of wireless & mobile communication and multimedia technologies. Advances in Wireless and Mobile Communications (AWMC) is an international research journal, which publishes top-level work from all areas of wireless communications systems, based on radio and infrared transmission mechanisms, and utilizing such technologies as cellular telephony, personal communications systems, and wireless local area networks. Areas and subareas of interest include (but are not limited to)